The Effect Of Giving Honey on The Process of Wound Healing in Burned Patients - Intan Pramesty (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Backgroud: Burns are one of the most dangerous injuries and the main cause of disability to death. Burns can be interpreted as one of the serious problems in society and are recorded to cause around 265,000 deaths each year. Honey can maintain the wound condition to keep it moist and in high viscosity to prevent infection. Method: This study was conducted to determine the effect of honey on the wound healing process in burn patients. This study uses a literature review method. The population in this study is a journal with a background in the health sector with 10 international journals on burns with the qualifications of 9 SCIMAGO indexed journals and 1 SINTA indexed journal published from 2015 to 2020. Results: Burns that treated in the form of pure honey can generate good results and heal in an average of 20 days. The healing process will be better, if the wound given a mixture of other ingredients which also have a low acidity such as garlic, chitosan and beeswax and olive oil. Honey has antimicrobial properties and a low pH level. The microbe most sensitive to honey is Staphylococcus aureus. Conclusion: The conclusion from this study, honey can be used as an alternative treatment for burns.